The rhythm of catalan: an analysis based on phonetically balanced texts - Patrícia Marsà Morales; Paolo Roseano (Estudios de Fonética Experimental)
Linguists have classified languages according to their rhythmic properties in two main classes, namely, stress-timed and syllable-timed languages. According to existing studies, the position of Catalan on this scale is controversial. The goal of this study is to better define the rhythmic properties of Catalan and to determine its status. We used a corpus containing phonetically balanced texts in three languages (Central Catalan, Central Peninsular Spanish and RP British English). We labelled the recordings with Praat and analysed several rhythmic parameters by means of the software Correlatore. Our data show that Catalan is definitely a syllable-timed language, like Spanish, although its position on the rhythmic scale is not as prototypical as the position of Spanish.